The Routledge companion to ecopoetics - Fiedorczuk, Julia; Newell, Mary; Quetchenbach, Bernard W., 1955-; Tierney, Orchid (New York : Routledge, 2024)
"The Routledge Companion to Ecopoetics offers a comprehensive coverage of the vital and growing movement of ecopoetics, charting the historical influences informing ecopoetics, delineating its various subdivisions, and presenting a global range of established figures and emerging scholarly debates. This volume begins with a general introduction to the field, followed by three major sections: Historical Contexts and Influences; Scalar Levels of Poetic Engagement, ranging from global through regional, terrain-oriented, local, and microscopic; and Intersections, examining poetic encounters with science, critical animal studies, philosophy, ethnobotany, environmental justice, visual and performing arts, disability studies, spirituality and ritual, and translation. The innovative second section will facilitate a comprehensive and systems-based sequencing, including ecopoetic engagements with topics including climate change, deforestation, extinction, pollution, toxicity, and disasters; fieldwork and close observation, and chemistry as it relates to environments including the human body. Each section will feature a broad overview and detailed consideration of poiesis, with reference to specific texts. The brand new essays in this book represent a wide variety of backgrounds, perspectives, and critical approaches exploring the interdisciplinary field of ecopoetics. Glossaries and cross-references will facilitate the volume's usefulness alongside its' global, interdisciplinary breadth to establish The Routledge Companion to Ecopoetics as a landmark textbook and reference for a variety of researchers and students"--
Keywords: Ecocriticism; LITERARY CRITICISM / General; POETRY / General